Traditional Games on Character Building: Integrating Hide and Seek on Learning - Asrial Asrial; Syahrial Syahrial; Dwi Agus Kurniawan; Muhammad Dewa Zulkhi (STAI Hubbulwathan Duri, 2021)
The purpose of this study was to determine the effect on learning of incorporating the traditional game of Hide and Seek. This type of research employs a mixed-methods. This study used several variables as research categories, including response, peace-loving character, and patriotism, and enrolled a total of 44 students. Descriptive and inferential statistics were used in the data analysis. The integration took place at an Elementary School and a Madrasah Ibtidaiyah in Batang Hari, as evidenced by the response, which reflected the peace-loving nature of patriotism. The result is that each response variable, peace, love, and patriotism, has a significant effect, with a value of sig 0.05, and that each variable is dominant in the good category.